Folic Acid Supplementation in a Mouse Model of Gestational Diabetes Alters Insulin Sensitivity in Mothers and Liver Methyl Metabolism and Beta Cell Mass in Fetal Offspring. (7th June 2021) - Mussai, Ei-Xia; Boonpattrawong, Nicha; Vanderkruk, Ben; Smith, Andre; Miller, Joshua; Devlin, Angela
Abstract: Objectives: Gestational diabetes (GDM) is associated with adverse outcomes in both mother and child. Women with diabetes and obesity (BMI ≥ 30kg/m 2 ) are recommended to take more folic acid than recommended for healthy women, to prevent birth defects. However, little is known about the effects of high folic acid supplementation in GDM. The objective of this study was to determine if folic acid supplementation in a mouse model of GDM affects maternal and fetal metabolic health. Methods: Female (C57BL/6J) mice were fed from weaning a control diet (10% kcal fat; control dams) or western diet (45% kcal fat; western dams; model of GDM) with (10mg/kg diet) or without (2mg/kg diet) supplemental folic acid (SFA). Dams were fed for 13 weeks prior to breeding. Physiological assessments of glucose homeostasis were conducted before breeding. Tissues were collected at gestational day 18.5 Results: Western dams had greater adiposity (p < 0.05), glucose intolerance (p < 0.01), and impaired β cell function (p < 0.05), confirming the model of GDM. Insulin sensitivity was reduced in SFA control dams (p < 0.05) but improved in SFA western dams (p < 0.05) compared to unsupplemented dams. Western dams had lower liver S -adenosylmethionine (SAM) and S -adenosylhomocysteine (SAH) (p < 0.05) compared to control dams; no effect of SFA was observed. SFA control and SFA western male offspring, but not female, had greater β cell mass (p = 0.058) compared to those from unsupplemented dams. Higher liver SAM was observed in SFA control and SFA western female offspring (p = 0.04), but not in male offspring. RNA sequencing identified 203 and 243 differentially expressed genes in liver from male SFA western offspring compared to western male offspring and SFA control male offspring, respectively (p < 0.05, FDR = 0.1). The differentially expressed genes were enriched in lipid metabolism pathways. In contrast, female SFA western offspring had only 12 differentially expressed genes in liver compared to SFA control offspring (p < 0.05, FDR = 0.1). Conclusions: Folic acid supplementation improved insulin sensitivity in dams fed a western diet and has sex-specific effects on fetal offspring β cell mass and liver methyl metabolism and gene expression. Funding Sources: CIHR.